Perlindungan terhadap Lingkungan dalam Perspektif Konstitusi - Faiz, Pan Mohamad (Jurnal Konstitusi, 2016)
Nowadays there is a tendency in many countries to protect the environment by incorporating general principles of environment into a state or a regional constitution. This article aims to examine the extent to which environmental protection can be provided through the adoption of those constitutional norms. This study was conducted using a qualitative methodology with a normative approach and library research derived from court decisions, law and regulations, books and journal articles. It concludes that the Indonesian Constitution contains constitutional norms for the environmental protection. However, these constitutional norms are still positioned as a subsidiary or supporting factor in the fulfillment of human rights and the national economy. In order to strengthen the environmental protection by the Indonesian Constitution, it requires a reformulation of related constitutional norms by positioning the environment more as the basic values in the state administration and national economic activities.